Implikasi Tes Objektif tipe Multiple Choice dalam PAS kelas 8 di SMP Muhammadiyah PK Kota Barat - Fadhilla Nangroe Anggraini; Ahmad Hakim Fathoniy; Haning Tyas Pratiwi; Nurul Latifatul Inayati (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
Objective tests are a type of assessment of learning activities that is experiencing developments in its renewal and implementation, therefore changes in the way of implementing types of tests for assessment, not all educational institutions have the same method. This research aims to reveal the implications of multiple choice as a form of objective assessment used in the End of Semester Assessment at Muhammadiyah PK Kotta Barat Junior Highschool. This research is a case study research using a descriptive qualitative approach. The method used in this research is observation and interview methods. The results of this research are that the West Kotta Special Program Muhammadiyah Middle School carried out a summative assessment using a multiple choice objective test. This policy has the advantage of assessing effectiveness in terms of time and over time. Based on the research results, researchers hope that when selecting the type of test in the End of Semester Assessment, aspects must be taken into account that influence students' ability to understand and answer the questions.